2012
DOI: 10.1177/0361684312454535
|View full text |Cite
|
Sign up to set email alerts
|

A Model Linking Diverse Women’s Child Sexual Abuse History With Sexual Risk Taking

Abstract: The purpose of our study was to examine the role that child sexual abuse may play in body surveillance and sexual risk behaviors among undergraduate women. First, a measured variable path analysis was conducted, which assessed the relations among a history of child sexual abuse, body surveillance, and sexual risk behaviors. Furthermore, body shame, sexual selfefficacy, and alexithymia were examined as intervening variables. Second, a multigroup path analysis was conducted comparing the hypothesized models appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 89 publications
(133 reference statements)
1
20
0
7
Order By: Relevance
“…Prior research supports the test-retest reliability (r 5 .67) and internal consistency of the measure (a s 5 .84-.90; Radloff, 1977). In addition, scores have been found to correlate moderately to strongly with other depression measures (self-report and clinician-administered) and to be sensitive to changes in symptomology following treatment (Weissman, Sholomskas, Pottenger, Prusoff, & Locke, 1977). In this study, Cronbach's alpha was .90.…”
Section: Methodssupporting
confidence: 68%
“…Prior research supports the test-retest reliability (r 5 .67) and internal consistency of the measure (a s 5 .84-.90; Radloff, 1977). In addition, scores have been found to correlate moderately to strongly with other depression measures (self-report and clinician-administered) and to be sensitive to changes in symptomology following treatment (Weissman, Sholomskas, Pottenger, Prusoff, & Locke, 1977). In this study, Cronbach's alpha was .90.…”
Section: Methodssupporting
confidence: 68%
“…Collectively the studies provide evidence that shame can hinder psychological adjustment following CSA. The quantitative studies demonstrate the centrality of shame, finding the presence of shame mediated a range of psychological outcomes, including the effectiveness of group psychotherapy on reducing PTSD symptoms (Ginzburg et al, ), sexual revictimisation in adulthood (Kessler & Bieschke, ) and body surveillance and alexithymia (Watson, Matheny, Gagné, Brack, & Ancis, ). Additionally, associations, were found between: shame and suicidal ideation (Kealy, Spidel, & Ogrodniczuk, ; Milligan & Andrews, ; You, Talbot, He, & Conner, ), self‐harming behaviours (Milligan & Andrews, ), dissociation (Talbot, Talbot, & Tu, ), body related trauma (Dyer, Feldman, & Borgmann, ), poor mental health (Rahm, Renck, & Ringsberg, ) and anxiety and depressive symptoms (Willie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research examining objectification theory among Black women presents a similarly complex picture. Although a number of cross-sectional studies suggest lower levels of self-surveillance (e.g., Breitkopft et al, 2007; Moradi & Huang, 2008) and body shame (e.g., Higgins, Lin, Alvarez, & Bardone-Cone, 2015) among Black women compared with White women, some studies suggest equivalent levels of self-surveillance (e.g., Fitzsimmons & Bardone-Cone, 2011; Watson, Matheny, Gagné, Brack, & Ancis, 2013) and body shame (e.g., Breitkopft et al, 2007) among these groups. Studies examining the pathways proposed by objectification theory have demonstrated support for the hypothesized connection between body surveillance and body shame (e.g., Buchanan, Fischer, Tokar, & Yoder, 2008; Watson et al, 2012) and between body shame and disordered eating symptoms (e.g., Higgins et al, 2015), though some research suggests that the connection between self-surveillance and disordered eating may not be supported in Black women (e.g., Fitzsimmons & Bardone-Cone, 2011).…”
Section: Introductionmentioning
confidence: 99%